2016
DOI: 10.31018/jans.v8i3.979
|View full text |Cite
|
Sign up to set email alerts
|

Growth, yield attributes, yield and economics of winter popcorn (Zea mays everta Sturt.) as influenced by planting time fertility level and plant population under late sown condition

Abstract: The field experiment was laid out in split plot design with three replications, assigning in 27 treatment combinations i.e. three sowing dates of Pop corn (Zea mays everta Sturt.)cv. V.L. Amber (15 Dec, 30 Dec and 15 Jan) arranged in main plots and three level of plant population (60000, 80000 and 100,000 plants ha-1) in sub plot. Three level of fertility (100:50:50, 150:65:65 and 200:85:85 kg of N: P2O5: K2O ha-1) apportioned in sub-sub plots at the Research farm, Institute of Agricultural Sciences, BHU, Vara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The higher gross return and net return in these interactions were due to higher grain and stover yield, whereas significantly lower gross return and net return were recorded with planting during 1 st week of November along with application of 100 % RDF was due to its lower productivity of crop 70 .…”
Section: Bio-economicsmentioning
confidence: 88%
“…The higher gross return and net return in these interactions were due to higher grain and stover yield, whereas significantly lower gross return and net return were recorded with planting during 1 st week of November along with application of 100 % RDF was due to its lower productivity of crop 70 .…”
Section: Bio-economicsmentioning
confidence: 88%
“…The higher physiological efficiency was recorded during 1 st week of November which might be due to more capacity of the plant to increase yield with per unit nutrient uptake. The lesser the application of fertilizer, the higher will be the nutrient use efficiency [ 5 , 61 , 71 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interaction effect showed that significantly higher gross return and net return were recorded with planting during 1 st week of October along with the application of 200% RDF and were on par with planting during 2 nd week of October with 200% RDF and planting during 1 st week of October with 150% The higher gross return and net return in these interactions were due to higher grain and stover yield, whereas significantly lower gross return and net return were recorded with planting during 1 st week of November along with the application of 100% RDF was due to its lower productivity of crop [ 76 ]. A significantly higher B-C ratio was recorded with sowing at 1 st week of October along with the application of 150% RDF (2.55) and lower was with sowing at 1 st week of November along with the application of 100% RDF (1.83).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation